Delivery of high quality stroke and vision care: experiences of UK services. Issue 8 (9th April 2016) - Rowe, Fiona; Walker, Marion; Rockliffe, Janet; Pollock, Alex; Noonan, Carmel; Howard, Claire; Currie, Jim
Abstract: Purpose : We sought to identify exemplars of high quality care provision from established stroke vision services. Methods : We identified areas of high quality services across the UK, judged as having integrated stroke/vision care provision for stroke survivors. Healthcare professionals were selected to participate in 1:1 interviews or focus groups. A strengths–weaknesses–opportunities–threats (SWOT) framework was used to lead the discussion in a semi-structured format. Thematic analysis was undertaken. Results : Interviewees ( n = 24) from 14 NHS Trusts included eye clinic managers, nurses, orthoptists, occupational therapists and physiotherapists. Identified strengths of their services included established communication, training provision for stroke team staff, "open access" for referrals, use of standardised screening/referral forms, provision of lay summaries and information sheets, patients assessed on the stroke unit with continued follow-up and initial visual assessments made within 1 week of stroke onset. Weaknesses included lack of funding, insufficient orthoptic cover, and time consuming retraining of stroke staff because of staff rotation and changes. Opportunities included increasing the number (or length) of orthoptic sessions and training of stroke staff. Perceived threats related to funding and increased appointment waiting times. Conclusions : Practical elements for improved stroke and vision care provision are highlighted which can be implemented with relatively little financial inputs. Implications for Rehabilitation: Integrated vision services within stroke units can improve the detection of visual problems in stroke survivors leading to earlier visual rehabilitation. Orthoptists within core stroke teams are beneficial to the delivery of a high quality service. This study illustrates clear practical elements to support the provision of high quality integrated stroke and vision services. Relatively little financial inputs are required to fund such services but with larger potential to improve patient care.